PENGEMBANGAN MODUL ELEKTRONIK MENGGUNAKAN STRATEGI 7E LEARNING CYCLE UNTUK PEMBELAJARAN KIMIA KELAS XI PADA MATERI KESETIMBANGAN KIMIA - Lisdiana, Hayyun; Dian Triwidiastuti; Tiwi Nur Astuti (University of Bengkulu, 2025)
This study aims to develop an electronic module using the 7E Learning Cycle strategy in chemistry learning in the form of a flipbook on chemical equilibrium for grade XI. The research method used is Research and Development (RnD) with the ADDIE research model, which includes the stages of analysis, product design, product development, product implementation, and final evaluation of the product. The research is based on the limited use of digital technology in learning and the lack of variation in teaching materials used during the lessons. Based on the needs analysis, there is a need for improvement in the presentation of teaching materials to make them more varied. The expert validation results indicate that the developed electronic module is valid and feasible to use. Based on the trial results of the electronic module, a satisfaction percentage of 89% was obtained, indicating that this electronic module is able to attract students' interest in learning chemistry because it is practical to use Keywords: Electronic Module, Chemical Equilibrium, 7E Learning Cycle, Learning Chemistry